Social economy and living well in the urban context: An institutional experience in Medellin, Colombia - Jiménez Inchima, Indira Isabel; Gómez Hernández, Esperanza (Cooperativismo & Desarrollo, 2017)
Introduction: This article presents the results of the study carried out in the associative productive units that arise in the framework of the solidarity economy program, developed by the municipal government of Medellín. The intention is that of showing the scope and limitations that these types of proposals have to strengthen other forms of organization and alternative production based on solidarity, as well as for improving the quality of life of the people who make part of them. Methodology: A qualitative study was carried out with direct in depth interviews done to different actors that participate or have participated in the municipal government’s solidarity economy program. Results: Because a market economy is still being consolidated, an instrumentalized notion of quality of life prevails. This makes invisible other meanings and dimensions of life, which emerge with the conceptions of living well that belong to the analyzed context. Conclusions: Major challenges still persist to strengthen the solidarity economy in Medellín, an economy based on other types of production, exchange and cooperation relations, and that reinforces a solidary subject.